The Influence of Person-Job Fit and Transformational Leadership on Performance at the Msme Bakpia Pathok 25 Pathok Jaya with Power Distance as a Moderating Variable - Irfan Marulitua Doloksaribu; Syamsul Hadi; Epsilandri Septyarini (Dinasti Publisher, 2025)
This study aims to simultaneously analyze the influence of person-job fit and transformational leadership on employee performance, as well as examine how power distance acts as a moderating variable in this relationship. A quantitative approach with a causal method was used to test the cause-and-effect relationships between variables. The population of this research includes all 200 employees of Bakpia Pathok 25 Pathok Jaya, with a sample of 134 respondents selected through stratified sampling based on work divisions. Data were collected using a questionnaire, and data analysis techniques included descriptive statistics, classical assumption tests (normality, multicollinearity, and heteroscedasticity tests), and hypothesis testing using T-test, F-test, and coefficient of determination (R²) analysis. The results showed that person-job fit had a negative effect on performance, indicating that lower compatibility between individuals and their jobs leads to decreased employee performance. On the other hand, transformational leadership had a positive effect on performance, showing that a strong transformational leadership style can enhance employee performance. However, power distance as a moderating variable did not strengthen the effect of either person-job fit or transformational leadership on performance. Thus, although power distance plays a role in organizational dynamics, it does not serve as a decisive factor in reinforcing the relationship between leadership or job fit and employee performance. These findings have important implications for human resource management in creating an effective and adaptive work environment.